The Religious and Political Revisions of The Prelude - S. Wiehl, John (Romanticism on the Net, 2018)
William Wordsworth's multi-decade revision of his poetic masterwork, The Prelude took many forms. In revising this massive work, Wordsworth reduced references to himself as performing a priestly role and to poetry as being ritualistic while increasing references to the vivid belief of the “ancient church” of early Christianity. These concerns mirror the central thrust of the Oxford Movement (or Tractarianism), a push for doctrinal reform within the Anglican church that was a reaction against the political successes of religious minorities and newly-minted, non-landowning voters. Current religiously-oriented criticism of the poem often attacks advancements in secularity, much like Wordsworth's revisions seem to sit uncomfortably alongside the development of a multi-confessional state.